UTILIZING INTERACTIVE LEARNING MEDIA TO ENHANCE FOURTH GRADE STUDENTS’ UNDERSTANDING OF PLANT PARTS FUNCTIONS AT SD NEGERI 52 LUBUKLINGGAU - Intan Permata Kusuma (Teaching and General Education Studies, 2025)
This study aims to develop and test the effectiveness of interactive learning media in improving the learning outcomes of Grade IV students of SD Negeri 52 Lubuklinggau on science materials about the function of plant parts. The background of this research is based on students' low understanding of abstract scientific concepts and the limited learning media available in schools. Using a Research and Development (R&D) approach with the Borg and Gall development model, the interactive media was systematically designed and validated by experts. The validation results indicated that the media fell into the "very feasible" category, and students rated it highly attractive. Testing of learning outcomes showed a significant increase from an average pre-test score of 64.5 to 84.5 in the post-test, confirming the effectiveness of the interactive learning media in enhancing student understanding. The media stimulated active engagement, supported visual and concrete comprehension, and significantly increased motivation to learn. In conclusion, the use of interactive media in science lessons can improve student understanding and engagement, making learning more effective and enjoyable. Future research is recommended to explore the integration of interactive media with collaborative learning strategies and to examine its long-term impact on student retention and critical thinking skills.